Karen's haircut - Martin, Ann M.; Farina, Katy (2023)
"Karen feels like an ugly duckling. She already has to wear glasses, and now her baby teeth are falling out, too. Fortunately, she knows exactly what will make her look glamorous -- a new haircut. But the beauty parlor lady cuts Karen's hair all wrong! Karen is devastated and worried about what the kids at school will say. Can Karen get back to feeling like her usual confident self?"--
Ages 7-10
Grades 2-3